Impact of Mindfulness and Alexithymia on Self-Concept: A Comprehensive Cross-Sectional Analysis - Motevalli, Saeid; Su, Jing; Ma, Wenwen; Song, Rui (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This research aimed to explore the predictive impact of mindfulness and alexithymia on individuals' self-concept. Utilizing a cross-sectional study design, data were collected from 400 participants through standardized instruments: the Five Facet Mindfulness Questionnaire (FFMQ) for assessing mindfulness, the Toronto Alexithymia Scale (TAS-20) for measuring alexithymia, and the Self-Description Questionnaire III (SDQIII) for evaluating self-concept. Statistical analysis, including descriptive statistics and multiple linear regression, was performed using SPSS version 27 to determine the predictive relationships between the variables. The analysis revealed that mindfulness and alexithymia significantly predict self-concept. Specifically, higher levels of mindfulness were associated with a more positive self-concept, whereas elevated alexithymia levels correlated with a more negative self-concept. The model accounted for 37% of the variance in self-concept scores, indicating a strong influence of these psychological constructs on individual self-perception. The study highlights the critical roles of mindfulness and alexithymia in determining self-concept. It suggests that mindfulness interventions could be particularly beneficial for individuals with high alexithymia levels, potentially aiding in the development of a healthier self-concept. These findings offer valuable insights for psychological practice and underscore the importance of addressing both mindfulness and alexithymia in therapeutic settings.